The Effectiveness of a Web-Based Self-Help Program to Reduce Alcohol Use Among Adults With Drinking Patterns Considered Harmful, Hazardous, or Suggestive of Dependence in Four Low- and Middle-Income Countries: Randomized Controlled Trial - Michael P Schaub; Marcela Tiburcio; Nora Martínez-Vélez; Atul Ambekar; Roshan Bhad; Andreas Wenger; Christian Baumgartner; Dzianis Padruchny; Sergey Osipchik; Vladimir Poznyak; Dag Rekve; Fabricio Landi Moraes; et al. (JMIR Publications, 2021)
BackgroundGiven the scarcity of alcohol prevention and use disorder treatments in many low- and middle-income countries (LMICs), the World Health Organization has launched an eHealth portal that includes the web-based self-help program "Alcohol e-Health." ObjectiveWe aimed to test the effectiveness of the Alcohol e-Health program in a randomized controlled trial. MethodsThis was a two-arm, individually randomized, and controlled trial across four LMICs comparing the self-help program and a psychoeducation and internet access as usual waiting list. Participants were broadly recruited from community samples in Belarus, Brazil, India, and Mexico from January 2016 through January 2019. The primary outcome measure was change in the Alcohol Use Disorders Identification Test (AUDIT) score with a time frame of 6 months between baseline and follow-up. Secondary outcomes included self-reported numbers of standard drinks over the previous week and cessation of harmful or hazardous drinking (AUDIT score <8). ResultsFor this study, we recruited 1400 predominantly male (n=982, 70.1%) at least harmful or hazardous alcohol drinkers. The mean age was 37.6 years (SD 10.5). The participants were recruited from Brazil (n=587), Mexico (n=509), India (n=212), and Belarus (n=92). Overall, complete case analysis identified higher AUDIT changes in the intervention group (B=−4.18, 95% CI −5.42 to −2.93, P<.001, d=0.56) that were mirrored by changes in weekly standard drinks (B=−9.34, 95% CI −15.90 to −2.77, P=.005, d=0.28) and cessation rates for harmful or hazardous drinking (χ21=14.56, N=561, P<.001). The supplementary intention-to-treat analyses largely confirmed these initial results. ConclusionsThe expansion of the Alcohol e-Health program to other LMICs with underdeveloped alcohol prevention and treatment systems for alcohol use disorders should be considered after successful replication of the present results. Trial RegistrationISRCTN ISRCTN14037475; https://www.isrctn.com/ISRCTN14037475 International Registered Report Identifier (IRRID)RR2-10.1111/add.14034